Academic writing: principles and practice in the context of philological education - Elena S. Ostrovskaya; Olga V. Vyshegorodtseva (Высшее образование в России, 2022)
The focus of the article is the place of Academic Writing in English in the overall system of courses and the university curricula of philological faculties (schools of linguistic and literary studies), general principles of such courses and ways and challenges of their implementation. The theoretical part is followed by a case study: the Academic Writing (English) course taught at the Faculty of Philology (School of Linguistic and Literary Studies) of the Higher School of Economics.